Tobacco chippers seeking assistance for smoking cessation: a case series - Pires,Gabriel Natan (2012)
OBJECTIVE: To describe a series of cases of tobacco chippers (TCs) who sought assistance for smoking cessation. DESCRIPTION OF CASES: We describe the case of three TCs who participated in a free quit-smoking support group. Smokers answered self-administered questionnaires covering sociodemographic data, smoking history, nicotine dependence, perceived health status, and motivational stages. Of the 183 smokers enrolled in the program, three (1.6%) were considered TCs. All three were women and reported alcohol use, although at low frequencies. Two of them reported the presence of potentially tobacco-related disease. All TCs presented light nicotine dependence and reported difficulties quitting smoking. All dropped out after the first group meeting. COMMENTS: This study describes a subgroup of smokers not extensively described in the literature: TCs seeking assistance for smoking cessation, with some degree of nicotine dependence, and who do not adhere to regular group therapy. Interventions aimed at this population may be an interesting strategy for smoking cessation.